Feasibility and acceptability of cognitive rehabilitation during the acute phase of schizophrenia. Issue 3 (26th March 2020) - Nemoto, Takahiro; Takeshi, Kiyoaki; Niimura, Hidehito; Tobe, Miki; Ito, Ryosuke; Kojima, Akiko; Saito, Hiroko; Funatogawa, Tomoyuki; Yamaguchi, Taiju; Katagiri, Naoyuki; Tsujino, Naohisa; Mizuno, Masafumi
Abstract: Aim: Although numerous studies have demonstrated promising results for the cognitive rehabilitation in subjects with schizophrenia, the efficacy of cognitive rehabilitation for everyday and social functioning is not yet sufficient. Although consideration of the contents and methods are vital, the timing for implementing cognitive rehabilitation also seems to be crucial. The aim of this study was to examine the feasibility and acceptability of cognitive rehabilitation during the acute phase of schizophrenia. Methods: Patients were recruited from consecutive acute admissions to the inpatient unit during a 15‐month period and were evaluated to determine whether they could be enrolled in an 8‐week cognitive rehabilitation program within 14 days of their hospital admission. Cognitive rehabilitation programs with a workbook style were adopted, taking the patients' conditions and burdens into consideration. Results: Eighty‐three patients were newly admitted during the entry period, and 49 patients (59.0%) were eligible for inclusion. Of them, 22 patients (44.9%) agreed to participate and started the program. Sixteen patients completed the program and underwent a second assessment. Thus, 32.7% (16/49) of all the eligible patients actually completed the study. The participants were quite satisfied with the program. Conclusions: This preliminary study yielded encouraging data demonstrating the feasibility and acceptability of cognitive remediation for patients with schizophrenia during the acute phase. The provision of cognitive rehabilitation during the acute phase of the first episode can reasonably be expected to lead to better functional outcomes.